Neonatal gut microbiota associates with childhood multisensitized atopy and T cell differentiation - Fujimura, Kei E; Sitarik, Alexandra R; Havstad, Suzanne; Lin, Din L; Levan, Sophia; Fadrosh, Douglas; Panzer, Ariane R; LaMere, Brandon; Rackaityte, Elze; Lukacs, Nicholas W; Wegienka, Ganesa; Boushey, Homer A; et al. (Nature medicine, 2016)
Differences in the composition of the gut microbiota of infants associate with relative risk of atopy in childhood, and metabolites linked with these distinct microbial states alter T cell differentiation ex vivo . Gut microbiota bacterial depletions and altered metabolic activity at 3 months are implicated in childhood atopy and asthma 1 . We hypothesized that compositionally distinct human neonatal gut microbiota (NGM) exist, and are differentially related to relative risk (RR) of childhood atopy and asthma. Using stool samples ( n = 298; aged 1–11 months) from a US birth cohort and 16S rRNA sequencing, neonates (median age, 35 d) were divisible into three microbiota composition states (NGM1–3). Each incurred a substantially different RR for multisensitized atopy at age 2 years and doctor-diagnosed asthma at age 4 years. The highest risk group, labeled NGM3, showed lower relative abundance of certain bacteria (for example, Bifidobacterium, Akkermansia and Faecalibacterium) , higher relative abundance of particular fungi ( Candida and Rhodotorula ) and a distinct fecal metabolome enriched for pro-inflammatory metabolites. Ex vivo culture of human adult peripheral T cells with sterile fecal water from NGM3 subjects increased the proportion of CD4 + cells producing interleukin (IL)-4 and reduced the relative abundance of CD4 + CD25 + FOXP3 + cells. 12,13-DiHOME, enriched in NGM3 versus lower-risk NGM states, recapitulated the effect of NGM3 fecal water on relative CD4 + CD25 + FOXP3 + cell abundance. These findings suggest that neonatal gut microbiome dysbiosis might promote CD4 + T cell dysfunction associated with childhood atopy.